A hexaplex PCR detection system for the identification of five human Plasmodium species with internal control - Chew, C. H.; Lim, Y. A. L.; Lee, P. C.; Mahmud, R.; Chua, K. H. (American Society for Microbiology, 2012)
Malaria remains as one of the major killers of humankind and persists to threaten the lives of more than one-third of the world's population. Given that human malaria can now be caused by five species of Plasmodium, i.e., Plasmodium falciparum, Plasmodium vivax, Plasmodium malariae, Plasmodium ovale, and the recent inclusion of Plasmodium knowlesi, there is a critical need not only to augment global health efforts in malaria control but more importantly to develop a rapid, accurate, species-sensitive/-specific and economically-effective diagnosis for malaria caused by these five species. Therefore, in the present study, a straightforward single step hexaplex PCR system targeting five human Plasmodium 18S small subunit ribosomal RNA (ssu rRNA) were designed and the system has successfully detected all five human malaria parasites. In addition, this system enables the differentiation of single infection as well as mixed infections up to two species level. This assay was validated with 50 randomly blind test and 184 clinical samples suspected with malaria. This hexaplex PCR system is not only an ideal alternative for routine malaria diagnosis in laboratories with conventional PCR machines but also adds value to diagnosis when there is a lack of experienced microscopist or/and when the parasite morphology is confusing. Indeed, this system will definitely enhance the accuracy and accelerate the speed in the diagnosis of malaria as well as improve the efficacy in malaria treatment and control, in addition to providing reliable data in epidemiological surveillance studies.